Pengaruh Profitabilitas Terhadap Return Saham PT Sorini Agro Asia Corporindo Tbk Tahun 2006 - 2011 - Yusi Hartini; Agus Sutardjo; Lestari Wuryanti (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2013)
PT Sorini Agro Asia Corporindo Tbk is a company engaged in industrial starch and sorbitolderivatives known polyols, the company will require additional funding to expand its operations inorder to meet increasing market demand for finance companies with share capital and equity capital.PT Sorini Agro Asia Corporindo Tbk continues to improve its financial performance to increase thecompany's share value and attract investors. The financial performance of the company can be seen byanalyzing the company's financial statements, analysis tools used are profitability ratios represented bythe net profit margin (NPM), return on investment as (ROI), return on equity (ROE), and earnings pershare (EPS). This study aimed to determine the effect of profitability on stock price returns PT SoriniAgro Asia Corporindo Tbk partially or simultaneously. Based on the analysis of financial statementsconducted in PT Sorini Agro Asia Corporindo Tbk period 2006 to 2011 is partially the result that thereturn on investment as a variable ROI and EPS significantly influence the stock price return, whilethe NPM and ROE does not significantly influence the stock price return. Simultaneously NPM, ROI,and EPS significantly influence stock prices and dipeoreh return results that EPS is a variable that hasthe greatest influence on the price return stock. Value ajusted R Square of 0.996, which means that theshare price return 99.6% influenced by NPM, ROI, and EPS. While the rest of 0.4% can be explainedby other variables outside the model.Keywords: Stock Price Return, NPM, ROI, ROE, and EPS